V.1 (New Delhi, 2012)
International communication plays a multifaceted role in the social, political, economic and cultural constellations of power. Research abounds in this dynamic field ranging from areas like international informational and cultural flows and the geopolitics of information to communication and development and the role of media and propaganda in conflict and international military interventions. This four-volume set brings together classic publications with less-accessible articles to trace the foundations and development of international communication as a field of inquiry. It reflects the growing internationalization of the field - with clearly defined volumes covering key aspects of international communication - from historical literature to regional perspectives and cultural and political writings on communication from across the globe.
Keywords: "Communication,international"